Maruyama Masao and Modern Japanese Political Thought - K. C., Khadaga (WILAYAH: The International Journal of East Asian Studies, 2015)
Maruyama Masao is one of Japan's influential political thinkers of the twentieth century. This article attempts to briefly discuss Maruyama Masao's thoughts on Japanese political engagement by focusing on the intellectual and psychological causes of Japan's political ambitions over the years. Maruyama Masao commented on numerous issues like the intellectual history of Tokugawa Japan, theory and psychology of ultra-nationalism and reflections on article IX of the Japanese Constitution. Maruyama's modern thought helped the Japanese understand their role in nation building and the importance of preserving peace at all cost. The paper concludes that Maruyama's political thoughts are still relevant in this day and age.